Exercise preconditioning and resveratrol reduce the susceptibility of rats with obstructive jaundice to endotoxin and alleviate lung injury - Li, Xujiong; Li, Wei; Wang, Tao; Li, Yan; Zhao, Li (Frontiers in Immunology, 2024)
IntroductionEndotoxemia is a common issue for patients with biliary obstruction. The lung is the most affected organ by endotoxins. Exercise training can alleviate lipopolysaccharide (LPS)-induced lung inflammation and resveratrol has biological effects similar to exercise. In this study, we evaluated the protective effects of exercise preconditioning, resveratrol, and their combination on LPS-induced lung injury and mortality in rats with obstructive jaundice.MethodsEndotoxemia was simulated in rats by common bile duct ligation (CBDL) and intraperitoneal injection of low-dose LPS. The treatment groups were pretreated with exercise and/or resveratrol to assess their effects on lung injury and mortality. Immunohistochemistry, immunofluorescence, and ELISA were subsequently used to evaluate the impact of exercise and/or resveratrol on inflammation in lung tissue and bronchoalveolar lavage fluid.ResultsWe found that even in the early stages, compared to sham-LPS rats, low-dose LPS induced excessive systemic inflammatory responses in CBDL rats, as evidenced by a significant increase in TNF-α and IL-6, severe lung inflammation, lung injury, and higher mortality rates, indicating that cholestasis increased rats’ susceptibility to endotoxins. Exercise training reduced neutrophil infiltration in the lungs of model rats and IL-6 levels in bronchoalveolar lavage fluid. Both exercise training and resveratrol exhibited synergistic effects in reducing macrophage accumulation in lung tissues, lowering TNF-α and IL-6 levels in the lungs, and decreasing TNF-α concentration in bronchoalveolar lavage fluid. Additionally, exercise and combined interventions both significantly increased the expression of IL-10. The interventions induced a marked improvement in lung tissue pathological damage and lung edema in model rats and prolonged the survival time of rats with obstructive jaundice.DiscussionThis study demonstrates that exercise preconditioning and/or resveratrol can significantly reduce rats’ susceptibility to endotoxins after CBDL and alleviate lung injuries through their anti-inflammatory effects, thereby decreasing the mortality risk.